Clean : A Mindspace Investigations Novel - Hughes, Alex (Alexandra Capell) (Hughes, Alex (Alexandra Capell) Mindspace Investigations novel., 2012)
"I used to work for the Telepath's Guild before they kicked me out for a drug habit that wasn't entirely my fault. Now I work for the cops, helping Homicide Detective Isabella Cherabino put killers behind bars. My ability to get inside the twisted minds of suspects makes me the best interrogator in the department. But the normals keep me on a short leash. When the Tech Wars ripped the world apart, the Guild stepped up to save it. But they had to get scary to do it-- real scary. Now the cops don't trust the telepaths, the Guild doesn't trust me, a serial killer is stalking the city-- and I'm aching for a fix. But I need to solve this case. Fast. I've just had a vision of the future: I'm the next to die"--Page 4 of cover.